Cluster approach in organization of transportation in the Baltic Sea Region - Nežerenko, Olga; Koppel, Ott; Tuisk, Tarmo (Transport, 2017)
The urgency of the issues discussed in this paper stems from the fact that cross-border collaboration is an essential part of commercial transportation today. With the extension of multimodal transportation concept, the efficiency and performance of not only national but also of regional transport systems depend on a synergy which occurs as a result of cooperation between transport enterprises and different modes of transport. The present study analyses the situation of transportation field in the Baltic Sea Region (BSR) in the period 2004–2011. The methodology used is based on Hierarchical Cluster Analysis (HCA), correlation analysis, Bayesian analysis and affinity analysis, which help to identify countries with similar trends in the field of transportation and the common reasons and factors which have led to the emergence of these clusters.First published online: 14 Jan 2015